2020
DOI: 10.1186/s13148-020-00866-w
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell DNA methylation sequencing reveals epigenetic alterations in mouse oocytes superovulated with different dosages of gonadotropins

Abstract: Background: Epigenetic abnormalities caused by superovulation have recently attracted increasing attention. Superovulation with exogenous hormones may prevent oocytes from establishing an appropriate epigenetic state, and this effect may extend to the methylation programming in preimplantation embryos, as de novo DNA methylation is a function of developmental stage of follicles and oocyte size. Follicle-stimulating hormone (FSH) and human menopausal gonadotropin (hMG) are common gonadotropins used for superovu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Instead we propose a model whereby the superovulation treatment stops the oocytes prematurely on their way to attain the proper size and natural quality. A similar proposal has been made in an independent study, on the basis of DNA methylation data in superovulated vs. naturally ovulated mouse oocytes 27 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Instead we propose a model whereby the superovulation treatment stops the oocytes prematurely on their way to attain the proper size and natural quality. A similar proposal has been made in an independent study, on the basis of DNA methylation data in superovulated vs. naturally ovulated mouse oocytes 27 .…”
Section: Discussionsupporting
confidence: 64%
“…If the above model is correct, then the logical follow-up experiment is to allow for more time until the release of the oocytes from the ovary, expecting to see a relief of the superovulation-associated deficits. Unlike the gonadotropin dosage 27,79,80 and the time of gonadotropin stimulation in relation to estrous cycle 81 and photoperiod 82 , the interval of the gonadotropins has not received much consideration, although it goes by itself that the accumulation of gene products in oocytes is a function of time during oogenesis. Compared to the natural length of the ovarian cycle in F1 mice, which is 4 days 83 , the interval eCG-hCG of the conventional superovulation spans only 2 days, thereby triggering the idea to assess the extent of preovulatory maturation attained until the administration of hCG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 , 40 These epigenetic alterations may be associated with the infertility backgrounds of parents, superovulation, or factors associated with the ART procedure. 41 , 42 The alterations may persist into childhood and be associated with worsened cardiovascular health among offspring. 33 , 34 Second, increased oxidative stress (OS) may also be associated with altered cardiac structure and function among offspring conceived by ART.…”
Section: Discussionmentioning
confidence: 99%
“…They also added that DNA methylation of superovulated oocytes obtained from prepubertal mice differs from the that of adult oocytes, while oocytes from superovulated adult females or naturally ovulated oocytes show slight differences. Similarly, Huo et al (Huo et al 2020 ) analyzed the effect of different dosages of FSH/hMG combined with hCG in female mice and found that superovulation causes methylation alterations at a specific set of loci, and the differentially methylated regions mainly occurred in regions other than promoters many of which are involved in vital biological processes such as glucose metabolism, nervous system development, cell cycle, cell proliferation, and embryo implantation. In the current study, we did not find any differences between IV group, in which mice were hormonally (5 IU PMSG and HCG) stimulated, and Vas group, not hormonally stimulated, in Dnmt1 and 3a and also global DNA methylation in MII stage oocytes.…”
Section: Discussionmentioning
confidence: 99%